Does Transcranial Direct Current Stimulation (tDCS) Improve Disgust Regulation Through Imagery Rescripting? - Fink, Jakob; Exner, Cornelia (Frontiers in Human Neuroscience, 2019)
The first pilot studies have shown the potential of imagery rescripting (ImR) for reducing con-tamination-related pathological disgust, although the effects were rather small. The aim of the present study is to investigate whether the effects of ImR in reducing disgust can be further increased by transcranial direct current stimulation (tDCS). tDCS is a non-invasive method of brain stimulation that has been successfully used multiple times to support emotion-regulation strategies. In the present study, disgust was induced via images related to individualized sources of disgust. Fifty-eight healthy volunteers took part in two parallel experiments. The two groups were matched by age, highest educational level and gender, and were tested under two emotion-regulation conditions, namely an ImR condition and a control condition. Partici-pants performed three trials on the first day and three trials on the second day. Across both days they performed three trials under each of the two emotion-regulation conditions in a randomized order. On one day active stimulation was applied, while on the other day participants were sham stimulated. The combination of emotion-regulation and stimulation condition was balanced across subjects. The only difference between the two groups was the localization of tDCS stimulation: one group was stimulated over the dorsolateral prefrontal cortex and the other group was stimulated over the visual cortex. This experimental manipulation was implemented to gain further insights into the underlying neuropsychological mechanisms of imagery. ImR was conducted via a previously-recorded audio file. The results confirm the effect of ImR on the reduction of disgust. However, with the present experimental design we were not able to show that supplementary tDCS of the visual cortex or the dorsolateral prefrontal cortex lead to improvement.